2016
DOI: 10.1016/j.jcct.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular area on non-contrast cardiac computed tomography as a predictor of incident heart failure – The Multi-Ethnic Study of Atherosclerosis

Abstract: Background The use of non-contrast computed tomography (nCT) measurements to predict heart failure (HF) has not been studied. In the present study we evaluated the prognostic value of left ventricular area adjusted for the body surface area (LVA-BSA) measured by nCT to predict incident HF and cardiovascular disease (CVD) events. Methods We studied 6781 participants (mean age: was 62 ± 10 years, 53% females; 62% non-white) free from prior HF in the MESA study who underwent nCT to evaluate left ventricular dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Recent studies have shown that increased CAC is associated with higher rate of cerebrovascular accidents [3536], heart failure [3738], and atrial fibrillation [39]. In addition, compared to individuals who have no CAC, those with increased CAC are more likely to have other non-cardiac conditions such as cancer, chronic kidney disease, chronic obstructive pulmonary disease, and hip fractures [40].…”
Section: What Are the Implication Of Cac Testing Beyond Chd?mentioning
confidence: 99%
“…Recent studies have shown that increased CAC is associated with higher rate of cerebrovascular accidents [3536], heart failure [3738], and atrial fibrillation [39]. In addition, compared to individuals who have no CAC, those with increased CAC are more likely to have other non-cardiac conditions such as cancer, chronic kidney disease, chronic obstructive pulmonary disease, and hip fractures [40].…”
Section: What Are the Implication Of Cac Testing Beyond Chd?mentioning
confidence: 99%
“…A substantially lower number of studies considered findings from CMR or CCT, reflecting the still limited availability and relatively high costs of these techniques with 11 respect to TTE. Several imaging modalities were investigated in the MESA cohort (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), although no head-to-head comparison between the different techniques has been carried out so far.…”
Section: Discussionmentioning
confidence: 99%
“…In a CCT study on the same population, left ventricular area [measured in mid-diastole and normalized for body surface area (BSA)] displayed a significant association with incident heart failure (hazard ratio 1.10 per 100 mm 2 /m 2 , P < 0.001) after adjustment for clinical variables and coronary artery calcium (CAC) score. 8 Conversely, left ventricular end-diastolic diameter at baseline did not independently predict incident including heart failure among elderly individuals. 34 Regarding left ventricular shape, a high index of sphericity on CMR imaging was a strong, independent predictor of heart failure in a model, including clinical variables, left ventricular end-diastolic volume index, left ventricular mass index, LVEF and N-terminal fraction of pro-B-type natriuretic peptide (hazard ratio 2.13, 95% CI 1.30-3.49).…”
Section: Left Ventricular Size and Shapementioning
confidence: 96%
See 1 more Smart Citation
“…Advanced CAD phenotyping, incorporating these structures, may leverage additional information and improve risk stratification. For example, epicardial adipose tissue, size of individual cardiac chambers, or CT-derived cardiac function has been related to adverse CV events beyond coronary stenosis and clinical risk factors [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%